PENINGKATAN PRESTASI BELAJAR BIOLOGI SISWA KELAS X IPA 1 SMA NEGERI 1 MERANGIN MELALUI METODE PROJECT DENGAN PENILAIAN PRESENTASI DAN POSTER TAHUN PELAJARAN 2021/2022 - Misrita Jalal (LP3M | STKIP YPM Bangko, 2022)
Implementing the discussion method in studying the topic of Biology, especially in learning about the environment, leaves students unable to apply in real life what they have learned in school. Because of that, in this research, the Project Method through group work was used in the task of recycling both organic an inorganic waste. The goal of this research was to enhance the students’ affective, cognitive, and psychomotor ability. The research Project took the form of class action research carried out in two cycles, both of which consisted of planning, implementing, observing, and reflection. The results of the research showed that by implementing the Project Method, the ability of the students increased in all three aspects: the cognitive aspect as evidenced by the daily test scores, the affective aspect as was apparent in the students initiative in making posters to raise environmental awareness, and in the psychomotor aspect made clear by the recycled products that were produced. The results of the overall reflection between the initial conditions before the action was taken until after the action was taken, both cycle I and cycle II showed an increase in student learning achievement, both from the cognitive, psychomotor and affective aspects. Between the initial conditions before the action to after the first cycle of action, there was an increase in cognitive value. More important than increasing cognitive values ​​is that teachers who previously were only able to reveal aspects of students' cognitive abilities, after taking action in the form of implementing project methods in the form of recycling waste with presentations and environmental poster assessments, now teachers have been able to reveal aspects of psychomotor abilities and students' affective aspects. Meanwhile, between cycle I and cycle II, there was an increase in student achievement from all aspects of student abilities. The real change that appears between the initial conditions, after the first cycle of action and the second cycle of action is an increase in the achievement of KKM. From 58% in the initial condition, to 82% after the first cycle of action and to 92% after the second cycle of action